2016
DOI: 10.1038/npp.2016.246
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Glucagon-like Peptide-1 Receptor Signaling in the Nucleus Tractus Solitarius is Required for Food Intake Control

Abstract: Alhough the glucagon-like peptide-1 (GLP-1) system is critical to energy balance control and is a target for obesity pharmacotherapies, the receptor-population-mediating effects of endogenous GLP-1 signaling are not fully understood. To address this, we developed a novel adeno-associated virus (AAV-GLP-1R) that utilizes short hairpin RNA to chronically knock down GLP-1 receptors (GLP-1R) in rats. As pharmacological studies highlight the hindbrain nucleus tractus solitarius (NTS) as a brain region important for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 53 publications
6
60
1
Order By: Relevance
“…A forebrain tissue block containing the BST was mounted onto the cryostat chuck, and thin sections were examined under a fluorescence microscope (model 80i, Nikon) until GFP-expressing cells were visualized within the alBST injection site. Bilateral BST micropunches (1 mm 3 ) of GFP-labeled tissue were collected and kept frozen for subsequent qRT-PCR analysis, using previously reported primers and procedures (Alhadeff et al, 2017). Total RNA was extracted from micropunches using TRIzol (Thermo Fisher Scientific) and the RNeasy kit (Qiagen).…”
Section: Quantitative Analysis Of Glp1r Mrna Knockdownmentioning
confidence: 99%
See 1 more Smart Citation
“…A forebrain tissue block containing the BST was mounted onto the cryostat chuck, and thin sections were examined under a fluorescence microscope (model 80i, Nikon) until GFP-expressing cells were visualized within the alBST injection site. Bilateral BST micropunches (1 mm 3 ) of GFP-labeled tissue were collected and kept frozen for subsequent qRT-PCR analysis, using previously reported primers and procedures (Alhadeff et al, 2017). Total RNA was extracted from micropunches using TRIzol (Thermo Fisher Scientific) and the RNeasy kit (Qiagen).…”
Section: Quantitative Analysis Of Glp1r Mrna Knockdownmentioning
confidence: 99%
“…TaqMan gene expression kits and PCR reagents (Applied Biosystems) were used to quantify the relative levels of translatable mRNA for GLP1R (GLP1r, Rn00562406) relative to rat GAPDH mRNA (Gapdh, Rn01775763_g1). Relative mRNA expression was calculated using the comparative Ct method, as previously described (Hayes et al, 2010;Alhadeff et al, 2017). qRT-PCR data from 2 of the original 16 rats prepared for analysis (n ϭ 1/AAV injection group) were subsequently discarded due to technical errors during RNA isolation and cDNA synthesis.…”
Section: Quantitative Analysis Of Glp1r Mrna Knockdownmentioning
confidence: 99%
“…For example, rats increase food intake when GLP-1 receptor antagonists are administered into the 4th ventricle or directly into the cNTS (Hayes et al 2009). Additionally, results from studies study utilizing viral-mediated knockdown of either PPG or GLP-1 receptor within the cNTS indicate that GLP-1 signaling is critical for both short- and long-term regulation of food intake (Barrera et al 2011; Alhadeff et al 2016). Together, these results indicate that GLP-1 signaling in the caudal brainstem (and potentially other central target sites) is necessary for normal feeding control, and also is sufficient to suppress intake.…”
Section: Cnts Modulation Of Stress-induced Hypophagiamentioning
confidence: 99%
“…Much of the existing work on the anorectic effects of GLP-1 is heavily focused on GLP-1 signaling through metabolic control nuclei including nuclei of the hypothalamus and the nucleus of the solitary tract [2830]. Recent work, however, has demonstrated that that GLP-1 also decreases food intake by reducing the rewarding value of food [3134], implicating a physiological role for the peptide beyond energy balance regulation.…”
Section: Introductionmentioning
confidence: 99%